Kerawanan Gelombang Pasang terhadap Penggunaan Lahan di Kawasan Wisata Pantai Sepanjang-Drini, Pesisir Selatan Kabupaten Gunungkidul - Prabawa, Bayu Argadyanto; Wahyuhana, Ratika Tulus; Fatchurohman, Hendy (Universitas Negeri Yogyakarta, 2024)
Gunungkidul Regional Spatial Plan states that Sepanjang and Drini Beach are designated areas for tourism zone, even Drini Beach is included in the development of a Fish Landing Base in Gunungkidul. The fact is that the Sepanjang-Drini coastal area is one of the susceptible area to storm tide that occur repeatedly every year. This research aims to study the land use susceptibility in the Sepanjang-Pantai Drini coastal area based on the storm tide model. Tidal wave analysis conducted by modeling inundation caused by run-up height of tidal waves scenario, that overlayed with land use map. The susceptible area to tidal waves based on 2.99 meter wave height scenario in the Sepanjang Coast to Drini Beach is 4.82 hectares. The land use that mostly affected by tidal waves is an open area land use of sand beach. Stalls are the ones most susceptible building to tidal waves, where there are at least 130 units located in tidal waves susceptible area.